Age-stratified gut microbial changes in diarrheal calves: insights from 16S rRNA sequencing across early development - Zhang, Yanli; Li, Chunfu; Tang, Luyang; Li, Fenqi; Fu, Xuanrong; Hao, Yu; Li, Jian; Feng, Xinyu; Hu, Wei (Frontiers in Microbiology, 2025)
IntroductionNeonatal calf diarrhea (NCD) remains a leading cause of mortality in calves under 1 month, yet how gut microbial responses vary across developmental stages remains unexplored. This study investigates age-stratified microbiome dynamics during NCD to enable precision interventions.Materials and methodsThis study investigated 60 female Holstein calves (1, 21, and 30 days old) from a commercial dairy farm, equally divided between healthy and diarrheal groups based on standardized fecal scoring. Fecal samples were collected aseptically, flash-frozen, and processed for 16S rRNA gene sequencing (V3-V4 region) using Illumina NovaSeq. Bioinformatics analyses included DADA2 pipeline for ASV calling, SILVA 138 database for taxonomic annotation, ANCOM-BC2 for differential abundance analysis (FDR < 0.05), PICRUSt2 for functional prediction, and SparCC networks (|r| > 0.6, p < 0.001) with Gephi visualization. Multivariate statistics, including PERMANOVA and canonical correspondence analysis were performed in QIIME2 and R (phyloseq/vegan packages), with all analyses rarefied to 39,161 sequences/sample.ResultsThe gut microbiome exhibited age-dependent succession, transitioning from Pseudomonadota dominance (47.2 ± 0.7%) at day 1 to Bacillota/Bacteroidota co-dominance (85.5 ± 8.2%) by day 30. Age explained significantly more compositional variance than diarrhea status (3.68% vs. 1.96%, p < 0.001). Three distinct age-specific diarrheal patterns emerged: (1) Early-stage (1-day-old) showed Bacillota/Pseudomonadota imbalances (84% of differential ASVs) with reduced network complexity (total node count, total edge count, average degree and modularity); (2) Mid-lactation (21-day-old) featured Kurthia as both significantly enriched (log2FC = 5.32) and a network hub (degree = 14); (3) Mature microbiota (30-day-old) displayed complex multi-phylum dysbiosis involving 10 metabolic pathways. Clostridia_UCG-014 persisted across diarrheal networks, while healthy calves showed age-progressive increases in microbial connectivity (edges: 125 to 1,104). Only 2 ASVs demonstrated consistent differential abundance across age groups, confirming the temporal specificity of diarrheal dysbiosis.ConclusionNCD-associated dysbiosis progresses through distinct developmental phases, from resilient phylum-level shifts in neonates to complex network disruptions in mature microbiota. The identification of stage-specific biomarkers (e.g., day 21 Kurthia) opens new avenues for age-tailored probiotic therapies and early intervention strategies.